Evaluasi Manajemen Aset, Proteksi, dan Dana Pendidikan (Studi Kasus pada Bapak Hamid) - , Achmad Lutfie ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A successful businessman with lack of knowledge to manage their own wealth is not hard to find. They tend to do business and manage their own wealth conventionally. One of the factors is the lack of education and information. In fact, many of the businesses man do not have a college degree, but successful in doing business and became rich. But usually their wealth focused on physical assets such as land, house, and also has no protection or planning for the future. Therefore, they need a service from wealth manager in managing their assets. The research focused on the family Mr Hamid which had a wife named Mrs Icah and had 4 children. Mr. Hamid has three grandchildren from the first and second child. Mr. Hamid worked as a technical director in a company providing construction services. Mr Hamid is a businessman and categorized HWNI (High Net worth Individual). The purpose of this study is to identify the client's risk profile, management and diversification of client assets, client protection and family planning education, and provide recommendations to the client in accordance with its current risk profile. The final results of this study indicate that the client has a risk profile that can tolerate high risk (above average risk taker). Client chose scenario 1 which contents of high-risk business ventures. Capital needed gain from selling one of the client's assets. This makes clientâs assets more diversified and increasing clientâs cash flow. Client also will have the protection of life insurance, vehicle insurance, fire insurance (for home), and the preparation of educational funding for clientâs youngest children.